2021
DOI: 10.1002/ece3.7819
|View full text |Cite
|
Sign up to set email alerts
|

Moderate plant–soil feedbacks have small effects on the biodiversity–productivity relationship: A field experiment

Abstract: Plant–soil feedback (PSF) has gained attention as a mechanism promoting plant growth and coexistence. However, most PSF research has measured monoculture growth in greenhouse conditions. Translating PSFs into effects on plant growth in field communities remains an important frontier for PSF research. Using a 4‐year, factorial field experiment in Jena, Germany, we measured the growth of nine grassland species on soils conditioned by each of the target species (i.e., 72 PSFs). Plant community models were paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 70 publications
(184 reference statements)
1
5
0
Order By: Relevance
“…These experiments, therefore, demonstrated that the plants created soil conditions in two years in the field that changed the subsequent plant growth. These plant growth responses have been reported elsewhere [42,43]. Here, we describe the soil microbial communities in the soils in these two experiments.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…These experiments, therefore, demonstrated that the plants created soil conditions in two years in the field that changed the subsequent plant growth. These plant growth responses have been reported elsewhere [42,43]. Here, we describe the soil microbial communities in the soils in these two experiments.…”
Section: Introductionsupporting
confidence: 76%
“…Aboveground plant biomass was harvested in these experiments. The plant biomass was, on average, ~25% different on 'self' than 'other' soil [42,43]. These experiments, therefore, demonstrated that the plants created soil conditions in two years in the field that changed the subsequent plant growth.…”
Section: Introductionmentioning
confidence: 72%
“…Conversely, subdominant plants with large PSFs, and dominant plants with small PSFs will have little effect on overyielding. For example, an experiment in Germany that used nine species and the same methodology as this experiment found a minimal role for PSF in biomass production (Grenzer et al, 2021). Broadly, PSF effects on community biomass reflected the specific plants and soil types present in a community, and not just the mean PSF across species.…”
Section: Discussionmentioning
confidence: 99%
“…Factorial experiments with more than three species remain uncommon within the plant–soil feedback literature, because factorial designs require large sample sizes (Crawford et al, 2019). For example, in a recent meta‐analysis 77% of the studies examined consisted of three species or less, and only three of the studies examined 10 or more species (Crawford et al, 2019; Kulmatiski, 2016; Maron et al, 2016; Petermann et al, 2008), although additional large PSF experiments not included in Crawford et al (2019) have recently been published (Grenzer et al, 2021; Heinen, Biere, et al, 2020). The relatively uncommon 16‐species factorial design of this study allowed us to examine how PSF varies across a relatively wide range of soil types (Figure 1a,b).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have investigated how PSFs affect plant productivity and diversity (Grenzer et al, 2021; Teste et al, 2017; Thakur et al, 2021). However, most of these studies focused on comparison of the effects of conspecific and heterospecific soils which were conditioned by single species (Zhao et al, 2018).…”
Section: Introductionmentioning
confidence: 99%